Decomposition of the most potent greenhouse gas (GHG) sulphur hexafluoride (SF6) using a dielectric barrier discharge (DBD) plasma. (19th April 2013) - Zhuang, Quan; Clements, Bruce; McFarlan, Andrew; Fasoyinu, Yemi
Abstract A DBD method has been developed to decompose sulphur hexafluoride (SF6) nearly 100% under conditions close to the exhaust gas in industries with energy efficiency of 0.015–0.15 GJ/ton carbon dioxide (CO2) equivalent, 1–2 orders of magnitude higher than CO2 capture and sequestration from power generation boilers. A typical test condition was SF6: 820 ppm; CO2/air: 50/50; gas flow rate: 623 mL/m at 25°C; AC voltage: 17–23 kV p–p; AC frequency: 7 kHz. The success of this project was due to the development of highly effective star‐shaped discharge elements and an improved design of the DBD system, that is mode of applying voltage, the physical aspects of the reactor.